INTERAKSI SOSIAL MELALUI MEDIA SOSIAL TIKTOK DI KALANGAN SISWA SMA PGRI 4 JAKARTA - Aurelia, Yunita (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The presence of TikTok has brought Gen-Z, most of whom are currently high school students, into the social media ecosystem which has a significant impact on their development as individuals and their social interactions with friends and students. Engagement in social media activities has become an important aspect of teenagers' lives. Teens often feel the need to use electronic devices as a means to build a positive social identity, express themselves, and connect with their peers. This research focuses on the use of social media TikTok in social interactions among SMA PGRI 4 Jakarta students. This study used descriptive qualitative method. This research was conducted at SMA PGRI 4 Jakarta Jl. Cipayung Raya, RT.1/RW.3, Kec. Cipayung, East Jakarta City. The informants in this research were five PGRI 4 SMA students who actively used TikTok. The results of this research found that PGRI 4 Jakarta High School students considered TikTok as a source of information that was easy to understand and useful. They use this platform to increase their academic knowledge and also to interact socially with fellow users.